Application of Learning Media Digital Pop-Up Books In Increase Ability Read Beginning of Children Aged 5-6 Years - Astutik, Rustiana Yuli; Tasuah, Neneng (BELIA: Early Childhood Education Papers, 2024)
Study this aim for know enhancement read start in children 5-6 years old based on application of learning media digital pop-up book at TK Mekar Sari 03 Soneyan, Margoyoso, Pati. Approach in study this use approach quantitative experiment with design Pre-experimental Design and with type One-Group Pretest-Posttest Design. subject in study this is child 5-6 years old. Retrieval technique sample using saturated sampling technique with use whole population of 30 children aged 5-6 years in Kindergarten Mekar Sari 03 Soneyan, District Margoyoso, Regency starch. Data collection techniques using observation, interview, questionnaire, and documentation. Data analysis techniques using statistics inferential with testing hypothesis use Paired Sample T-Test. Research results from t test calculation obtained value | t count | > t table , ie 21.60 > 2.04523, with score significance of 0.000, so Ho is rejected and Ha is accepted, meaning there is enhancement significant on ability read start child in a manner significant as big 33.46%. There is average difference in ability read start child 5-6 years old before and after given treatment. N-gain test results obtained value 0.60, so show that application of learning media inner digital pop-up book increase ability read start child is on the criteria medium. this show that learning media digital pop-up book can used in increase ability read start child.